Widely tunable single-mode slot waveguide quantum cascade laser array - Li, Jinghao (2022)
We report designs and experimental demonstrations of a widely tunable single-mode quantum cascade laser array based on slot waveguide structures in the mid-infrared region. The laser array device realized a continuous tuning range of 71 cm-1 from 9.66 μm to 10.37 μm at 300 K only using the current tuning without any external heatsink temperature adjustments, in good agreement with the design. Stable single-mode operations free of undesired mode-hops have been obtained over the whole tuning range. Another slot waveguide QCL array with a 41 cm-1 continuous tuning range around 7.3 μm has also been realized with the same design principle, demonstrating the universal applicability of the array design. The broadly continuous tuning with simple processing makes the array device a suitable candidate for mid-infrared sensing and spectroscopy application.